Density Distributions and Elastic Electron Scattering Form Factors of Proton-rich 8B, 17F, 17Ne, 23Al and 27P Nuclei - Noori, Rafah I.; Ridha, Arkan R. (Iraqi Journal of Science, 2019)
In this work, the nuclear density distributions, size radii and elastic electron scattering form factors are calculated for proton-rich 8B, 17F, 17Ne, 23Al and 27P nuclei using the radial wave functions of Woods-Saxon potential. The parameters of such potential for nuclei under study are generated so as to reproduce the experimentally available size radii and binding energies of the last nucleons on the Fermi surface.